PERUBAHAN SIFAT KIMIA DAN POPULASI MIKROBILOGI SELAMA FERMENTASI - Rujiah, Rujiah; Apriyanto, Mulono; Alfa, Akbar (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2024)
This study aims to determine changes in chemical properties in the fermentation of dried cocoa beans. Sun-dried cocoa beans obtained from farmers have a non-uniform moisture content. In order to minimize fermentation failure, dry cocoa beans are obtained by drying fresh cocoa beans using a dryer cabinet with previously conditioned temperatures such as drying with sunlight, and each sugar content is determined. Fermentation experiments of dried cocoa beans were carried out fermentation in fermentation containers with a number of beans of 150 grams per container. Before fermenting, dry cocoa beans are rehydrated so that the moisture content is close to fresh beans, then dried cocoa beans are incubated for six days without being turned over during fermentation. Each treatment was repeated three times and observed every 24 hours to 120 hours. The results showed that chemical and physical changes increased according to SNI. Penelitian ini bertujuan untuk mengetahui perubahan sifat kimia pada fermentasi biji kakao kering jemur. Biji kakao kering jemur yang diperoleh dari petani memiliki kadar air yang tidak seragam. Guna menimalkan kegagalan fermentasi maka biji kakao kering jemur diperoleh melalui pengeringan biji kakao segar menggunakan kabinet dryer dengan sebelumnya dikondisikan pada suhu seperti pengeringan dengan sinar matahari, dan masing ditentukan kadar gula reduksinya. Percobaan fermentasi biji kakao kering dilakukan fermentasi pada wadah fermentasi dengan jumlah biji 150 gram setiap wadah. Sebelum difermentasi terlebih dahulu biji kakao kering jemur di rehidrasi agar didapat kadar air mendekati biji segar, kemudian biji kakao kering jemur diinkubasi selama enam hari dan tanpa dibalik selama fermentasi. Setiap perlakuan diulangi tiga kali dan diamati tiap 24 jam sampai 120 jam. Hasil penelitian menunjukan perubahan kimia dan fisik mengalami peningkatan sesuai SNI.